Review on X-ray detectors based on scintillators and CMOS technology - Rocha, J. G. (2011)
This article describes the theoretical basis, design and implementation of X-ray microdetectors based on scintillating materials and CMOS technology. The working principle of such microdetectors consists in the absorption of X-rays by scintillators, which produce visible light. The visible light is then detected and converted into electric signals by means of photodetectors. In order to understand such detectors, several issues related to its implementation are presented in this article, namely: Production of X-rays and interaction between them and matter - the first step necessary to the detection of X-rays is that they must be absorbed by some material, in this case by a scintillator; Radiation detectors - there are several types of detectors, namely: pn junctions, photoconductors, based on thermal effects and scintillators; Fabrication of scintillator arrays - after the X-ray radiation is absorbed by a scintillator, this material emits visible light whose intensity is proportional to the total energy of the absorbed X-rays; Optical interfaces between scintillators and photodetectors - the visible light generated by scintillators must arrive to the photodetectors, so, it is necessary to have an interface between the scintillators and the photodetectors that ideally does not introduce losses; Photodetectors and interface electronics - the visible light is absorbed by the photodetectors and converted into electrical signals, which are finally converted into digital images by means of interface electronics. The article presents some promising patents on X-ray detectors based on scintillators and CMOS technology.